Supplemental information: photodegradation of bitumen-derived organics in oil sands process-affected water - Challis, Jonathan K.; Parajas, Angelique; Anderson, Julie C.; Asiedu, Evelyn; Martin, Jonathan W.; Wong, Charles S.; Ross, Matthew S. (My University, 2020)
Supplementary material consists of figures and tables.